Women Composers : The Lost Tradition Found - Jezic, Diane (Book collections on Project MUSE., 1994)
Though rarely included in traditional music history, women have a remarkable tradition as composers of Western music. This book brings together musical and biographical material on twenty-five women, from the eleventh through the twentieth centuries. Each chapter focuses on one composer, providing an introduction to her life, an analysis of her music, a checklist of her works, and a bibliography. Extensive appendices include a historical outline showing female composers in relation to their more famous male contemporaries by period and genre, and suggestions for further readings and recordings.